Medulloblastoma and ABO-Rh Blood Group: Evidence of an Association between the Distribution of Blood Group Antigens and Medulloblastoma - Ankur Bajaj; Rehana Ansari; Somil Jaiswal; Chhitij Srivastava; Bal Krishna Ojha; Imran Rizvi; Tulika Chandra (Indian Journal of Neurosurgery, 2024)
Objective Medulloblastoma is the most common central nervous system embryonal tumor and the most common malignant brain tumor of childhood. This study aims to find out the incidence of the ABO-Rh blood group in medulloblastoma patients of northern India to assess the utility of the blood group as a preclinical non-modifiable risk factor.